Effect of Seed Treatments, Packaging Materials and Storage Conditions on Seed Longevity in Onion (Allium cepa l.) - SONDARVA JYOTI; PATEL JB; VAGHASIYA KP; VORA DV (Seed Research, 2026)
An investigation was carried out from summer 2020 onwards to evaluate the effect of moisture resistant containers and treatments with botanicals on the storability of onion seeds stored at ambient and cold storage conditions. The experimental material comprising three different factors, storage conditions [S1: Ambient storage condition and S2: Cold storage condition (10 + 20C)]; packaging materials (P1: Plastic storage box, P2: Air tight plastic container, P3: Aluminium foil bag and P4: Aluminium foil bag with vacuum packing); and seed treatments (T1: Control, T2: Neem seed Kernel powder 5g/kg, T3: Sweet flag rhizome powder 5g/kg and T4: Black pepper powder 5g/kg) was carried out in Junagadh, Gujarat for 14 months. Germination percentage and other quality parameters evaluated at every 2 month’s interval decreased gradually, while seed moisture content with increased in storage period. Seeds packed in Aluminium foil bag with vacuum packing after seed treatment with sweet flag rhizome powder @ 5g/kg seed and stored in cold storage condition recorded the highest germination percentage and vigour, followed by seeds packed in Aluminium foil bag with vacuum packing after seed treatment with black pepper powder @ 5g/kg and stored in cold storage condition after fourteen months of storage period.